The involvement of exosomes in the diagnosis and treatment of pancreatic cancer - Ariston Gabriel, Abakundana Nsenga; Wang, Fang; Jiao, Qinlian; Yvette, Umwali; Yang, Xuemei; Al-Ameri, Samed Ahmed; Du, Lutao; Wang, Yun-shan; Wang, Chuanxin (Molecular cancer, 2020)
At the moment, pancreatic cancer is among the deadliest gastrointestinal diseases, and pancreatic cancer growth is a complex biological process that is based on different kinds of genes. Exosomes are extracellular vesicles containing microRNAs (miRNAs), messenger RNA (mRNA), and proteins, they act as the most prominent mediator of intercellular communication, and they regulate, instruct, and re-educate their surrounding microenvironment and target specific organs. Due to accumulative evidence proved that exosomes are involved in metastasis, cell proliferation, EMT, angiogenesis, and TME of pancreatic cancer, exosomes are crucial potential candidates to detect pancreatic cancer early. This review aims to convey the current understanding of the main functions employed by exosomes in early diagnosis and treatment of pancreatic cancer.